Barriers and Enablers of Emergency Remote Education amid COVID-19 Pandemic: Perspectives of English Language Teachers - Cahapay, Michael B; Labrador, Mark Gil P (International Journal of Educational Studies, 2021)
The aim of this paper is to describe the barriers and enablers in emergency remote education from the views of language teachers amid COVID-19 pandemic. It involved eleven purposively sampled high school English language teachers in the Philippines during the school year 2021-2022. The qualitative data were processed using thematic analysis technique. The results revealed two superordinate themes: 1.) barriers of emergency remote English language education and 2.) enablers of emergency remote English language education. Under the first superordinate theme, barriers of remote emergency education, three subordinate themes emerged: 1.1.) problems in internet connection and materials; 1.2.) unfamiliarity with remote instructional design; and 1.3.) lack of skills in using remote technologies. Furthermore, under the second superordinate theme, enablers of remote emergency education, three subordinate themes were revealed: 2.1.) self-learning in using technology; 2.2.) instructional accommodations; and 2.3.) school and community support. These study outcomes provide practical insights that shape emergency remote education amid the current novel crisis. The barriers should be addressed, and the enablers should be cultivated, so that a successful remote English language education can be attained.